A Future Approach of Muang Fai Irrigation Systems in Urban Area of Chiang Mai Province: A Systematic Review - Maneesatit, Paworn; Dankittikul, Chaiyasit (Journal of Landscape Architecture and Planning, 2025)
The Muang Fai irrigation system is a form of indigenous water management wisdom in Northern Thailand that has existed for centuries, deeply intertwined with the region’s culture, way of life, and community-based ecosystems. This article aims to explore future directions for the Muang Fai system through three key objectives: (1) to review the body of knowledge related to various aspects of the Muang Fai system, (2) to examine the transformation of the system within urban Chiang Mai, and (3) to propose approaches, models, and research methodologies that align with its future development. A systematic review of literature on the Muang Fai system was conducted across multiple dimensions. The study identifies five primary themes in existing research on Muang Fai: (1) geography, (2) history, society, and culture (3) economics and livelihoods, (4), legal frameworks, and (5) ecology and the environment. The Muang Fai system demonstrates several strengths, particularly its low-cost, highly efficient water management at the local community level and its role in reinforcing community resilience. However, significant transformations within urban Chiang Mai have arisen due to changes in social contexts, urban expansion, lifestyle shifts, and government policies—factors that critically affect the sustainability of the Muang Fai system. This article highlights existing knowledge gaps that warrant further study and proposes development strategies that align with contemporary social contexts. These include the integration of technology, geoinformatics systems, and community-based knowledge enhancement, ensuring that the Muang Fai system can evolve in harmony with modern and future societal dynamics.